1978
DOI: 10.1111/j.1365-2265.1978.tb02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Infusion Into the Portal and Peripheral Circulations of Unanaesthetized Dogs

Abstract: Changes in glucose, phosphate, potassium, non-esterified fatty acids (NEFA) and insulin in peripheral venous blood were compared in five unrestrained fasted dogs during different rates of insulin infusion by the portal and peripheral circulation. The 'low' rate of insulin infusion was that required to produce a fall in plasma glucose of 0.56-0.83 mmol/l (0.024 u/kg/h female, 0.012 u/kg/h male). Two-fold and four-fold higher rates are referred to as 'medium' and 'high' rates, respectively. In all dogs, dose-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…When meal insulin was infused initially, the animals receiving portal insulin had lower NEFA levels but toward the end of the meal infusion similar NEFA levels were observed indicating that maximum inhibition of lipolysis was present in both groups. Similar effects on NEFA in insulin infused dogs have been reported by others [13]. The comparison between the metabolic profiles in these two groups of diabetic animals brings out certain other significant differences.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…When meal insulin was infused initially, the animals receiving portal insulin had lower NEFA levels but toward the end of the meal infusion similar NEFA levels were observed indicating that maximum inhibition of lipolysis was present in both groups. Similar effects on NEFA in insulin infused dogs have been reported by others [13]. The comparison between the metabolic profiles in these two groups of diabetic animals brings out certain other significant differences.…”
Section: Discussionsupporting
confidence: 69%
“…Since the portal (natural) route is not readily accessible for experimental insulin replacement in man, a series of animal experiments in pancreatectomised dogs was conducted to evaluate this route of insulin replacement as compared with peripheral IV insulin administration. The effects of short term insulin infusions into the portal and peripheral circulations of unanaesthetised normal dogs have been reported [13].…”
mentioning
confidence: 99%
“…Several studies have shown that portal venous infusion of insulin can result in reduced circulating insulin levels, compared with peripheral venous infusion (24), probably associated with greater liver insulin extraction (25). It therefore stands that an insulin-induced, liver-mediated signal may have resulted in the restoration of lard intake to nondiabetic levels.…”
Section: Discussionmentioning
confidence: 99%
“…h before and '/4, xh, %, 1, VA, l'A, l3A, 2, 2!4, 3, 4, 5 and 6 h after terminating the infusion for measurement of calcium and phosphate as previously described (Stevenson et al 1978). Plasma 47Ca was meas¬ ured in a Packard Gamma Spectrometer and corrected for background.…”
Section: Methodsmentioning
confidence: 99%
“…A fresh minipump was implanted sc in the dog's back every 7 days and the infusion rate adjusted to produce plasma calcium increases of 0.4 to 0.7 mmol/I. After 4 weeks, each dog was prepared with two indwelling cannulae in the superior vena cava, the infusion cannula being 3 cm nearer the atrium than the cannula for blood sampling, as previously described (Stevenson et al 1978). The sc infusion was then replaced by an iv infusion of hPTH 1-34 at a rate designed to produce a similar plasma calcium increase.…”
mentioning
confidence: 99%